Impact of liberalization, economic growth and trade policies on current accounts of developing countries: An econometric study - Ashok Parikh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The objectives of this paper are to examine the impact of liberalization on trade deficits and current accounts for developing economies. Attempts at liberalization in trade could lead to an increase in imports in the short run and this could cause both trade and current account deficits in countries that adopt rapid liberalization. Liberalization could increase growth rates in the short run and this also could result into higher imports than exports. The study examines the data of 64 developing economies over the period 1970–99 and conducts a panel data study on the relationship between trade balance to GDP percentages with the growth rates controlling for other factors. Similar analysis is conducted using the current account to GDP percentages in the panel data framework. We consider the endogeneity of growth variable and lagged effects through a dynamic structure. We find that higher growth rates in developing economies result in greater trade and current account deficits although the sensitivity of such trade deficits to growth rates is not high. The higher growth rate in developed countries and improvement in income terms of trade of developing economies tends to reduce trade deficits and current account deficits of developing economies. Liberalization on its own has positive impact but combined with income terms of trade yields a negative overall impact on trade balance to GDP percentages. The impact of improvement in terms of trade and the higher growth in developed countries seems to play a greater role in improving trade balances than the corresponding deterioration induced by higher growth in developing economies. – liberalization ; panel data ; dynamic ; terms of trade ; oil
Keywords: F02; F32; C23; C33; O53; 330; Außenhandelsliberalisierung; Terms of Trade; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Wirtschaftswachstum; Entwicklungsländer